Talking (or Not) About Sexual Violence: Newspaper Coverage of the Confirmation Hearings of Justices Thomas and Kavanaugh - AbiNader, Millan A. (Journal of interpersonal violence, 2021)
The ways in which sexual violence is portrayed in the media contribute to communities’ understanding of violence and can influence survivor outcomes. The parallel cases of the confirmation hearings of Justices Kavanaugh and Thomas provide an opportunity to measure if and how the cultural zeitgeist has shifted around issues of sexual violence. This study sought to answer two questions: (a) When a supreme court nominee is accused of sexual violence, have the ways the mainstream media discussed the violence in newspaper headlines changed between 1991 and 2018? To what extent and how? (b) Have the ways the mainstream media characterizes the nominee and the accuser within and between 1991 and 2018 changed? How? Headlines were collected systematically from eight major U.S. newspapers, resulting in a data set of 373 headlines from 1991 and 249 from 2018. Qualitative thematic analysis was used to examine the characterizations of the accuser, nominee, and violence. Supplemental chi-square analyses were used to compare how violence was categorized in the two years. While less victim-blaming and minimization of sexual violence occurred in the 2018 headlines, newspapers continued to avoid naming the sexual violence. The characterizations of the nominee, accuser, and violence became depersonalized in 2018, focusing on politics rather than the people and issues at hand, likely reflecting a highly politicized American public. Despite the heightened attention to sexual violence that current movements have sparked, our analysis of comparable cases in 1991 and 2018 suggests newspaper headlines continued to avoid naming sexual violence as violence in 2018 as in 1991, and furthermore, contemporary language about sexual violence and its survivors and perpetrators has not changed to reflect an increased response to survivor healing and perpetrator change. Rather, shifts in language suggest survivors and perpetrators may be politicized as tools for parties and politicians to debate larger issues or stake political positions.